Mushroom production on digestate: Mineral composition of cultivation compost, mushrooms, spent mushroom compost and spent casing - Agnieszka Jasinska; Ketil Stoknes; Przemyslaw Niedzielski; Anna Budka; Miroslaw Mleczek (Journal of Agriculture and Food Research)
Produced in the process of anaerobic digestion, the effluent called digestate is rich in nutrients and can be used as a growing media for mushrooms. However, it can also be rich in non-essential and trace elements, heavy metals, various organic pollutants, pharmaceuticals, and other unwanted compounds with potential negative effects. Therefore, two button mushroom species, Agaricus bisporus (brown cultivar) and Agaricus subrufescens, were cultivated on digestate based substrate. The mineral composition of the experimental mushroom compost (EMC), mushrooms (M), spent mushroom compost (SMC) and spent casing (SC) was evaluated by means of ICP OES. Mineral distribution and quantity were substrate dependent, digestate origin was determined for most of investigated elements, excluding Ca, Mo, Pb, Ce and Nd, where the source was straw. However, content of elements with high mobility such as Cd, Cu, Pb and Zn for EMC was low. Short composting method for mushroom compost preparation used in this study could be suitable method for reducing available Cd, Cr, Ni, Pb, Zn and total As. For the casing material, bark was richer in major essential elements (MEE's) and essential trace elements (ETE's), besides Ca, where peat indicated higher content (1490 mg kg-1). From the trace elements with detrimental health effects (TEWDHE) group, bark was richer in Ba and Pb, but peat contained significant content of As (3.92 mg kg-1). The results clearly indicated both the studied mushrooms are valuable source of K, Na and Se, while A. subrufescens provided higher amounts of Cu and Zn. No threat for human consumption for Ni, Pb, As, and Cd, their content is under the limits and decreases with each subsequent mushroom yield. SMC and SC were nutrient rich especially for Fe, Mg, Mn, Si and Zn, giving them added value as biobased product for boosting vegetable crop yield. However, Cr and Ni, ETS's for plants in lower amounts, were elevated in SMC/SC, therefore the mineral composition should be monitored. Low concentration of hazardous elements in the spent substrates allows for subsequent use.